EFFECTIVENESS OF PERICARP MANGOSTEEN EXTRACT AS NEFROPROTECTOR - Dewita, Gita (Majority, 2015)
Abstract Kidney is the main organ of elimination for all drugs used orally, but in certain limits kidneys can not perform its function in the elimination of drugs, causing drug accumulation in the kidneys that can cause injury in the renal proximal tubule. One of the herbal remedies that have the effect of nefroprotektor or inhibiting kidney damage is pericarp of mangosteen. The main content of it which has the effect of nefroprotektor is xanthon and its derivatives with biological activity as antioxidants, free radicals absorbers and inhibiting perisidasi of lipids. γ-mangostin inhibited changes in arachidonic acid to PGE2 in microsomal, it is possible that inhibition of the cyclooxygenase pathway can be inhibited inflammatory process. In addition, mangosteen pericarp has a pharmacological activity as an anti-allergic, anti-inflammatory, anti-microorganism, anti-oxidant, anti-cancer, anti-atherosclerotic and anti-HIV. Anti-oxidant and anti-inflammatory activity of natural mangosteen pericarp can inhibit inflammation and oxidative stress of hepatocytes and renal tubular cells, thus preventing cell damage. Keywords: cyclooxygenase pathway, free radicals, mangosteen pericarp extract, xanthon. Abstrak Ginjal merupakan organ eliminasi utama untuk seluruh obat yang digunakan peroral, namun pada batas-batas tertentu ginjal tidak dapat melakukan fungsinya dalam eliminasi obat sehingga menyebabkan tertimbunnya obat dalam ginjal yang dapat menyebabkan cedera di daerah tubulus proksimal ginjal. Salah satu obat herbal yang memiliki efek nefroprotektor atau efek menghambat kerusakan ginjal adalah kulit manggis. Kandungan utama kulit manggis yang memiliki efek nefroprotektor adalah xanthon dan derivatnya dengan aktivitas biologis sebagai antioksidan, peredam radikal bebas dan penghambat perisidasi lipid. γ-mangostin menghambat perubahan asam arakidonat menjadi PGE2 dalam mikrosomal, ini ada kemungkinan penghambatan pada jalur siklooksigenase sehingga proses inflamasi bisa dihambat. Selain itu kulit buah manggis mempunyai aktivitas farmakologi sebagai anti alergi, anti inflamasi, anti mikroorganisme, anti oksidan, anti kanker, anti aterosklerosis maupun anti- HIV. Aktifitas antioksidan dan anti inflamasi alami dari kulit manggis ini yang dapat menghambat peradangan dan stress oksidatif dari sel hepatosit dan tubulus ginjal, sehingga mencegah kerusakan sel. Kata kunci: ekstrak kulit manggis, jalur siklooksigenase, radikal bebas, xanthon